PERAN SUPERVISI KLINIS DALAM PENINGKATAN KOMPETENSI DAN MOTIVASI BIDAN - Meyana Marbun; Keysha Iszmi Erhan; Amanda Sahfitri (Jurnal Minfo Polgan, 2022)
Midwives are the backbone of maternal and child health services, yet they often work in challenging conditions with limited support. Clinical supervision is a globally recognized key intervention for supporting and developing frontline health workers. This literature review aims to explore the role and effectiveness of clinical supervision in improving midwives' technical and non-technical competencies and work motivation. The review results indicate that structured, supportive, and ongoing clinical supervision is significantly positively correlated with improvements in clinical skills, adherence to practice standards, decision-making ability, self-confidence, job satisfaction, and intrinsic motivation. Effective supervision also helps reduce burnout and professional isolation, particularly in remote areas. Implementation challenges include lack of supervisor capacity, time constraints, and resistance to a culture of blame-based supervision. Optimizing clinical supervision requires investment in supervisor training, the development of a clear framework, and the creation of an organizational culture that supports learning and development.